1983
DOI: 10.1097/00003446-198305000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Development of Speech Intelligibility in Children with Recurrent Otitis Media

Abstract: This study defined developmental functions for PediatricSpeech Intelligibility word and sentence materials presented in quiet and in competition for 25 normal children and 25 children with recurrent otitis media. Ages ranged from 24 to 56 mos. In normal children, developmental functions for Pediatric Speech Intelligibility speech materials showed earlier development of performance (1) in quiet than in competition and (2) for words than for sentences (competing condition). In children with otitis media, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 6 publications
3
31
0
3
Order By: Relevance
“…Apparently, of the tests used in the present study, speech recognition in background competition is the task most sensitive to auditory deprivation. This is consistent with the findings of previous studies of auditory perceptual ability in children (Brandes & Ehinger, 1981;Gravel & Wallace, 1992;Jerger et al, 1983;Moore et al, 1991;Pillsbury et al, 1991) that have demonstrated performance on competitive listening tasks to be most consistently affected by OME.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Apparently, of the tests used in the present study, speech recognition in background competition is the task most sensitive to auditory deprivation. This is consistent with the findings of previous studies of auditory perceptual ability in children (Brandes & Ehinger, 1981;Gravel & Wallace, 1992;Jerger et al, 1983;Moore et al, 1991;Pillsbury et al, 1991) that have demonstrated performance on competitive listening tasks to be most consistently affected by OME.…”
Section: Discussionsupporting
confidence: 92%
“…In most previous studies using similar test procedures (Brandes & Ehinger, 1981;Hoffman-Lawless et al, 1981;Jerger et al, 1983;Pillsbury et al, 1991;Webster et al, 1989;Welsh et al, 19831, cases and controls were selected on the basis of retrospectively collected OME data and therefore subject to recruitment biases. The current data might therefore give a more reliable impression of the association between OME and some aspects of auditory perception at school age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An effect of long lasting OME on auditory processing [29] and speech perception has been described [30][31][32][33]. A study by Gravel et al did not confirm this effect [34].…”
Section: Relation Between the Galker Test And Hearing Tympanometry mentioning
confidence: 99%
“…The results of many investigations, among which several carefully designed longi tudinal studies, suggest a relationship be tween early OME and later language and edu-cational skills, at least for children up to 4 years of age [1][2][3]. Psychophysical studies have shown that children with a history of OME produce deviating results on several types of speech recognition tests [1,[4][5][6]. In general, effects of early OME on auditory pro cessing have been found in short-term evalua tions but to a lesser degree in the long term [4,5,7], This could mean that there is a gradual recovery of auditory processing capabilities after the OME episodes (and the associated hearing loss) have been resolved.…”
Section: Introductionmentioning
confidence: 99%